Functional status, lymphocyte-to-monocyte ratio, and platelet-to-lymphocyte ratio as prognostic factors of one-year survival rate in elderly patients with advanced-stage non-small cell lung cancer - Ratna Nurhayati; Aulia Rizka; Cleopas Martin Rumende; Noorwati Sutandyo; Arif Hanafi; Edy Rizal Wahyudi; Hamzah Shatri; Anna Mira Lubis; Em Yunir; Muhammad Firdaus; Yuniar Harris Prayitno; Nadira Nibras Taqiyya (Cancer Treatment and Research Communications)
Background and aim: Non-small cell lung cancer (NSCLC) is the most common lung cancer found in elderly patients. Aging and chronic inflammation are related to its pathogenesis. Functional status, lymphocyte-to-monocyte ratio and platelet-to-lymphocyte ratio describe a chronic inflammation and correlate to the survival of older adults with advanced-stage (IIIB-IV) NSCLC. This study aims to determine functional status, lymphocyte-to-monocyte ratio and platelet-to-lymphocyte ratio as prognostic factors to 1-year survival in elderly patients with NSCLC stage IIIB-IV. Methods: Survival analysis with a cohort retrospective study is conducted on elderly patients with NSCLC stage IIIB-IV in Dharmais National Cancer Center Hospital between January 2020 and June 2022. Medical records were collected, comprising complete blood count prior to chemotherapy or radiotherapy, assessment of functional status through the Barthel Index for Activities of Daily Living (ADL), and 1-year survival post-diagnosis. Factors potentially influencing outcomes included diabetes mellitus, anemia, chronic obstructive pulmonary disease, and chronic kidney disease. Statistical analyses were performed using SPSS 20.0, employing the log-rank method for bivariate analysis and Cox regression for multivariate analysis. Results: In a cohort of 108 patients, the majority were aged 60–69 years (74.1 %), male (66.7 %), diagnosed at stage IV (80.5 %), and with adenocarcinoma subtype (75.0 %). Significant correlations were observed between the lymphocyte-to-monocyte ratio and platelet-to-lymphocyte ratio with the 1-year survival rate in elderly patients with stage IIIB-IV NSCLC (p = 0.015 and p = 0.001, respectively). Functional status did not show a significant correlation with 1-year survival overall (p = 0.540), but significant correlations were noted in patients receiving chemotherapy (p = 0.044) and radiotherapy (p = 0.009). Conclusion: The lymphocyte-to-monocyte ratio and platelet-to-lymphocyte ratio provide significant prognostic insights regarding 1-year survival in elderly patients diagnosed with stage IIIB-IV non-small cell lung cancer (NSCLC). In contrast, the functional status of these patients does not demonstrate a significant correlation with one-year survival.